Nationalism revisited : Austrian social closure from romanticism to the digital age - Karner, Christian (Austrian and Habsburg studies, 2020)
"Focused on the German-speaking parts of the former Habsburg Empire, and on present-day Austria in particular, this book offers a series of highly innovative analyses of the interplay of nationalism's discursive and institutional facets. Here, Christian Karner develops a distinctive perspective on Austrian nationalism over the longue durée, tracing nationalistic ways of thinking and mobilizing from the late eighteenth century to the present. Through close analyses of key texts representing diverse settings and historical episodes, this book traces the connections, continuities and ruptures that have characterized the varieties of Austrian nationalism"--